A randomized clinical trial of the efficacy and safety of sitagliptin compared with dapagliflozin in patients with type 2 diabetes mellitus and mild renal insufficiency: The CompoSIT‐R study. Issue 12 (16th August 2018) - Scott, Russell; Morgan, Jerry; Zimmer, Zachary; Lam, Raymond L. H.; O'Neill, Edward A.; Kaufman, Keith D.; Engel, Samuel S.; Raji, Annaswamy
Abstract : Aim: To compare the efficacy and safety of the dipeptidyl peptidase‐4 inhibitor sitagliptin with the sodium‐glucose transporter‐2 inhibitor dapagliflozin in patients with type 2 diabetes and mild renal insufficiency. Materials and Methods: Patients with HbA1c ≥7.0 to ≤9.5% (≥53 to ≤80 mmol/mol) and estimated glomerular filtration rate ≥60 to <90 mL/min/1.73m 2 on metformin (≥1500 mg/d) ± sulfonylurea were randomized to sitagliptin 100 mg ( n = 307) or dapagliflozin 5 mg titrated to 10 mg ( n = 306) once daily for 24 weeks. A longitudinal data analysis model was used to test the primary hypothesis that sitagliptin is non‐inferior to dapagliflozin in reducing HbA1c at Week 24, with superiority to be tested if non‐inferiority is met.ClinicalTrials.gov NCT02532855. Results: Baseline mean HbA1c (% [mmol/mol]) was 7.7 (60.9) and 7.8 (61.2), and mean eGFR (mL/min/1.73m 2 ) was 79.4 and 76.9 for the sitagliptin and dapagliflozin groups, respectively. After 24 weeks, the between‐group difference in least squares mean (95% CI) changes from baseline in HbA1c was −0.15% (−0.26, −0.04) (−1.67 mmol/mol [−2.86, −0.48]), P = 0.006, meeting the prespecified criteria for declaring both non‐inferiority and superiority of sitagliptin versus dapagliflozin. The HbA1c goal of <7% (<53 mmol/mol) was met by 43% (sitagliptin) and 27% (dapagliflozin) of patients. No meaningful between‐group difference was observed in a pre‐specified analysis of 2‐hour incremental postprandial glucose excursion. A review of adverse events (AEs) was notable for a lower incidence of drug‐related AEs with sitagliptin compared with dapagliflozin. Conclusions: In patients with type 2 diabetes, mild renal insufficiency and inadequate glycaemic control on metformin ± sulfonylurea, sitagliptin treatment resulted in greater improvement in glycaemic control compared with dapagliflozin and was generally well tolerated.